Goal Oriented Activity Towards Life Skill Training: Preliminary Indications of a Task-intensive Approach to Manage Cerebral Palsy - Saumen Gupta; Kavitha Raja (Disability, CBR and Inclusive Development)
Purpose: To devise a viable programme of intervention for older people with Cerebral Palsy (CP). Methods: Using focus group interviews, a ‘top down’ model of intervention was devised among older children and adolescents with CP. Ten participants volunteered and a custom tailored approach was employed, in keeping with the participants’ goals. Results: The outcomes are described qualitatively. Conclusions: There are preliminary indications that the programme is versatile and feasible. Further trials must be conducted before conclusive comments can be made.